Software Architecture with C# 9 and .NET 5 : Architecting software solutions using microservices, DevOps, and design patterns for Azure, 2nd Edition /: Architecting software solutions using microservices, DevOps, and design patterns for Azure, 2nd Edition. (2020) - Baptista, Gabriel; Abbruzzese, Francesco
No abstract available